ANTIOXIDANT AND ANTIBACTERIAL ACTIVITIES OF FLAVONOID GLYCOSIDES FROM FICUS EXASPERATA VAHL-HOLL (MORACEAE) LEAVES. - Taiwo, Bamigboye Josiah; Igbeneghu, Oluwatoyin A. (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Ficus exasperata Vahl-Holl (Moraceae) leaves are used for infectious and inflammatory conditions in many West African Countries. However, there is need for more phytochemical studies to justify the ethnomedicinal uses of the plant. Material and Methods: The crude 50% aqueous ethanolic extract of the leaves was partitioned successively between water and; n-hexane, ethyl acetate and n-butanol. The fractions were subjected to antimicrobial activity using agar diffusion test. n-Butanol fraction, which showed both antimicrobial and radical scavenging activities was subjected to repeated chromatographic fractionation on both silica and Sephadex LH-20 columns. Each stage of the purification was monitored by thin layer chromatographic diphenylpicryl hydrazyl autographic assay. Three compounds were isolated. The structures of the compounds were elucidated using spectroscopic methods, shift reagent studies, acid hydrolysis, and by comparison with literature data. Results: The compounds were identified as apigenin C-8 glucoside (1), isoquercitrin-6-O-4-hydroxybenzoate (2) and quercetin-3-O-β-rhamnoside (3). The solvent fractions and isolated compounds were found to inhibit the growth of Gram +ve organisms only. Conclusion: These flavonoid glycosides are being reported in this plant species for the first time. Their weak in vitro antimicrobial activity suggest the flavonoids may be acting as pro-drug. The radical scavenging activity of the compounds may justify some of the ethnomedicinal uses of the plant as free radicals are implicated in the aetiology of many inflammatory diseases.